1983
DOI: 10.2307/3429509
|View full text |Cite
|
Sign up to set email alerts
|

Mutagenicity in Emissions from Coal- and Oil-Fired Boilers

Abstract: The mutagenicity of emission samples from three oil-fired and four coal-fired boilers have been compared by using the Salmonella/microsome assay. Very little or no mutagenic activity was observed in samples from five of these boilers. The sample from one oil-fired boiler showed mutagenic activity of about 500 revertants/MJ, and the sample from a coal-fired fluidized bed combustor had an activity of 58.000 revertants/MJ measured with strain TA 98 in the absence of metabolic activation. All samples contained sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

1983
1983
2012
2012

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 5 publications
0
7
0
Order By: Relevance
“…Generally the solventextractable organic composition of coal fly ash from modern pulverized coal plants is quite low. Similarily, gaseous emissions of organic compounds include ethylene, benzene, toluene, and a variety of alkanes (11). Large power plants fired with pulverized coal generally have efficient combustion and emit very small amounts of organic compounds whereas smaller boilers are often less efficient and produce greater concentrations or organic effluents (50).…”
Section: Coal-fired Power Plant Emissionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Generally the solventextractable organic composition of coal fly ash from modern pulverized coal plants is quite low. Similarily, gaseous emissions of organic compounds include ethylene, benzene, toluene, and a variety of alkanes (11). Large power plants fired with pulverized coal generally have efficient combustion and emit very small amounts of organic compounds whereas smaller boilers are often less efficient and produce greater concentrations or organic effluents (50).…”
Section: Coal-fired Power Plant Emissionsmentioning
confidence: 99%
“…Mutagenicity not detected with the Ames Salmonella assay with several samples has however been reported as positive in the mammalian V79 hamster cells assay (11,53). Technical difficulties have prevented measurement of the mutagenicity of the gas phase of coal-fired power plant emissions.…”
Section: Coal-fired Power Plant Emissionsmentioning
confidence: 99%
“…review by Chrisp and Fisher). 28 Mutagens from residential oil burning have been reported by Lewtas 174 and from coal-and oil-fired power plants and industrial boilers by M0ller and Alfheim 87 and Alfheim et al 18 Furthermore, mutagens have been found in emission samples from wood and peat combustion, 17>7M73 -' 74 cereal straw combustion,' 75 ' 176 and from fluidized bed coal combustors. 18 -177182 However, only a few of these studies have aimed at further characterization of the mutagens present.…”
Section: Stationary Combustion Sourcesmentioning
confidence: 93%
“…This discrepancy can easily be understood since later studies have shown a great variation in the mutagenic activity of fly ash from one plant to another. 18 Fisher et al 184 found that most mutagens were associated with the finest size fraction of the fly ash as found for particles from ambient air. Furthermore, they observed a variation of the mutagenic activity depending on the sampling temperature.…”
Section: Stationary Combustion Sourcesmentioning
confidence: 98%
See 1 more Smart Citation